Preparação e caracterização de materiais vítreos e vitrocerâmicos oxifluoretos à base de TeO2 - Freitas, Daniel De (2014)
In this study we prepared vitreous samples of composition TeO2-Nb2O5-PbF2, varying the parameters of obtaining samples, in order to minimize evaporation / sublimation of the components involved and to study their structural and optical properties. The samples obtained were analyzed for Differential Scanning Calorimetry (DSC) and X-Ray Diffraction. The glass domain was obtained. In glasses obtained were performed heat treatments in order to obtain glass ceramic. Heat treatments were performed close to the crystallization temperature (Tx) and heat treatments near the temperature of last crystallization peak, obtained by DSC. The glass ceramics samples were analyzed by same techniques used to analyze the vitreous samples.